High performance Multi Threshold voltage level converter for multi-VDD systems - Ahmad G.; Kumar Y.; Sahu P.K. (My University, 2025)
Multiple voltage supply systems are most efficient and commonly employed techniques for low power designs. The idea behind this technique is to use multiple supply voltages (multi-VDD) for a single chip by dividing the integrated circuit into regions, called voltage islands, operating at different voltages. In dual supply voltage circuits, when connecting a circuit having low voltage supply (VDDL) to a circuit having high voltage supply (VDDH), it is necessary to insert level converter at each low-to-high boundary as the interface to prevent the flow of static current. In this paper we have characterized the previously proposed Multi-Threshold voltage based level converters as well as proposed a new high performance level converter using Cadence Virtuoso tool in UMC 180nm standard CMOS technology. The proposed design offers up to 38.10% power reduction and up to 50.88% less Power Delay Product (PDP) than the existing level converters. © 2013 IEEE.